Code-mixing in the FM Radio in Bangladesh: A Sociolinguistic Observation - Hosain, Md Iqbal (IIUC Studies, 2016)
This paper deals with code-mixing used in the FM radio of Bangladesh. Code-mixing, a term in sociolinguistics, refers to the hybridization of two languages in a bilingual context. Of late, in the FMs of Bangladesh, the Radio Jockeys and the callers have frequently been mixing Bengali and English codes in their various programs. It is supposed to be the liberalization of the air waves that leads to the shifting of language in broadcasting by the RJs. In this paper, the researcher intends to extrapolate the motivations for code-mixing, and see whether the specific extralinguistic factors contribute to such code-mixing. Data from naturally occurring announcements and conversations were recorded from the four main radio stations, and then transcribed into English for analysis. IIUC Studies Vol.10 & 11 December 2014: 99-110